Essential Roles of Drosophila Inner Centromere Protein (Incenp) and Aurora B in Histone H3 Phosphorylation, Metaphase Chromosome Alignment, Kinetochore Disjunction, and Chromosome Segregation - Adams, RR (2001)
We have performed a biochemical and double- stranded RNA-mediated interference (RNAi) analysis of the role of two chromosomal passenger proteins, inner centromere protein (INCENP) and aurora B kinase, in cultured cells of Drosophila melanogaster . INCENP and aurora B function is tightly interlinked. The two proteins bind to each other in vitro, and DmINCENP is required for DmAurora B to localize properly in mitosis and function as a histone H3 kinase. DmAurora B is required for DmINCENP accumulation at centromeres and transfer to the spindle at anaphase. RNAi for either protein dramatically inhibited the ability of cells to achieve a normal metaphase chromosome alignment. Cells were not blocked in mitosis, however, and entered an aberrant anaphase characterized by defects in sister kinetochore disjunction and the presence of large amounts of amorphous lagging chromatin. Anaphase A chromosome movement appeared to be normal, however cytokinesis often failed. DmINCENP and DmAurora B are not required for the correct localization of the kinesin-like protein Pavarotti (ZEN-4/ CHO1/MKLP1) to the midbody at telophase. These experiments reveal that INCENP is required for aurora B kinase function and confirm that the chromosomal passengers have essential roles in mitosis.